Odpowiedzi

  • Użytkownik Zadane
2010-03-28T12:59:41+02:00
V=Pp x H
Pp a x b =6cm X 3cm=18cm2
V=18cm x 9cm=108cm2
V=Pp x H
Pp=a x b=6dm x 6dm=36dm2
V=36dm2 x 4.2dm=151.2cm2
V=Pp x H
Pp a x b=2m x 0.4m=0.8m2
V=0.8m2 x 0.28m=0.224m3
12 2 12
2010-03-28T13:00:12+02:00
V = a*b*c
P = 2ab+2bc+2ac = 2*(ab+bc+ca)

a) a=6cm b=3cm c=9cm
V=6*3*9 = 162 cm^3
P=2(6*3+3*9+9*6) = 2(18+27+54) = 2*99=198cm^2

b) a=6dm b=60cm c=4,2dm
a=60cm b=60cm c=42cm
V = 60*60*42=151200cm^3
P=2*(60*60+42*60+42*60)=2*8640=17280cm^2

c) a=2m b=0,4m c =2,8dm
a=200cm b=40cm c =28cm
V=200*40*28=224000cm^3
P=2(200*40+200*28+28*40) = 2*14720 = 29440cm^2
21 4 21